Multiple peer use of pivotal response training to increase social behaviors of classmates with autism: results from trained and untrained peers. - Pierce, K (1997)
Two children with autism and 8 typical peers participated in a study designed to replicate an earlier finding of successful social-skills intervention for children with autism using peer-implemented pivotal response training (PRT) and to assess the effects of using multiple peer trainers on generalization of treatment effects. During training, peers were taught PRT strategies using didactic instruction, modeling, role playing, and feedback. After treatment, children with autism engaged in increased levels of social behavior.